Ethnomathematical exploration of Cetho Temple on the topic of plane figures for elementary school - Riska Purnamasari; Agustiningsih Agustiningsih; Ridho Alfarisi (Ethnomathematics Journal, 2022)
Education and culture that exist in everyday life are closely related. In order to bridge the gap between culture and education, especially mathematics education, there is ethnomathematics. The existence of mathematics is inherent in everyday life, but many people are not aware of it. Examples of daily activities that contain elements of mathematics are calculating the price of groceries, and calculating the area and volume of certain buildings. The purpose of this study is to explore and describe the ethnomathematics of Cetho Temple and to examine the plane figures related to the basic competencies of fourth grade mathematics learning for elementary school students. This type of research is descriptive qualitative with data collection methods using observation, interviews, and documentation. Data analysis activities started from the instrument validation test, reduction, data presentation, and drawing conclusions. Triangulation technique was used to reduce bias during data analysis. The results showed that at Cetho Temple there was a geometric concept. The part of the temple that contains the concept of geometry, namely the statues, reliefs, and other important parts. The concept of geometry consists of the concept of the plane figures, spatial, polygonal, similar, and reflection. Based on these findings, the study focused on the flat structure material related to the basic competencies of fourth grade mathematics learning for elementary school students.